Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages in excess of record years) is reduced to 60 per cent. and will disappear at the end of the year. All the indirect taxation, with the exception of a few cases of purchase tax, is maintained so that the poorest continue to pay the same tax on an article as the very rich. Generous COMPENSATION is awarded to Bank of England stockholders and the coalowners, in spite of the latter's disastrous record. The Coal Act contains no more reference to the workers than if Mussolini had drafted it. The industrial output may be jeopardised this winter by a coal shortage of 5 million tons. Mr. Shinwell attributes the main cause to the shortage of manpower, yet he implores the men, whom Labour has failed to provide with a new incentive, to increase output. It is a sad reflection on Labour's financial policy that its first Budgets were hailed by booming quotations in the City, just as Mr. Bevin's foreign policy received most applause from the Tories. Round the turn of the year very important economic and financial problems shared public attention with purely political matters on the international front. The Labour Government, represented by a Liberal, Lord Keynes, and a Conservative, Lord Halifax, concluded the Loan Agreement with the U.S.A. It is obvious from questions in the House and statements elsewhere that the implications of the AMERICAN LOAN and the very special conditions attached thereto are even to-day understood by only a few. We need not join the Tory wailing about the possible loss of Imperial Preferences in consequence. To a consistent Socialist, any attempt to put an economic ring-fence round an Empire is a threat to world peace and trade. But Kingsley Martin, in the "New Statesman," implores the Labour Cabinet to refuse the Loan, if the shackling condition was insisted on that there must be no bilateral trade agreements in future ; Britain would no longer have the right to say to her Dominions, or to Russia, or to Denmark : "We will import from you if you will take imports from us." The Loan Agreement and its adjunct, the Bretton Woods Agreement relating the world's currencies to gold, clearly links Britain with U.S. economics. If it could be assumed for one moment that American Capitalism has become internationally minded and prepared to accept in future payment in goods from debtor-nations, Bretton Woods might be a step forward. As it is there is every indication that American Business is out for quick, ruthless profit making. To accept American tutelage for many years to come may have serious repercussions here when the next and inevitable slump in the States occurs. Moreover, the acceptance of the Loan is due to an underestimate of our own productive capacity and of the powers of understanding of the people, in spite of its war record. 23 15X/2/98/21